Synthesis of branched β-1, 3-glucan oligosaccharide with narrow degree of polymerization by fungi co-cultivation. (1st December 2021) - Wu, Jianrong; Yang, Zelin; Yang, Xuechen; Chen, Xiaotian; Zhang, Hongtao; Zhan, Xiaobei
Abstract: The large molecular weight and poor water solubility of β-1, 3-glucan impede its potential applications. In this study, the β-1, 3-glucan producing fungi and Trichoderma harzianum capable of secreting endo -β-1, 3-glucanase were co-cultivated to produce branched β-1, 3-glucan oligosaccharides (bOβGs) by fermentation with Sclerotium rolfsii and Schizophyllum commune. The highest bOβG yields from S. rolfsii in flasks were 4.53 and 9.94 g/L in a 7 L fermenter. Structural analysis proved that bOβG from S. rolfsii had a narrow degree of polymerization of 5–12, whereas bOβG from S. commune had a degree of polymerization of 5–15. Antioxidant tests showed that both bOβGs had remarkable DPPH radical scavenging activity and hydroxyl radical scavenging activity, and the activity of bOβG from S. commune was better than that of bOβG from S. rolfsii . In addition, bOβGs could promote the secretion of NO by mouse macrophages and increase the production of TNF-α, IL-1β, and IL-6 in RAW264.7.